ANALISIS FAKTOR-FAKTOR PENYEBAB KEMISKINAN DI PROVINSI RIAU - Silvieni Girsang; Lapeti Sari; Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Poverty is a situation where there is an inability to meet basic needs such as food, clothing, shelter, education, and health. Poverty is one of the problems for governments wishing to create a fair and equitable prosperity. Riau province which is rich in natural resources, especially oil, but there are still many people who belong to the category of Riau province of the poor. Based on the background can be formulated problem is what are the factors that cause poverty in Riau and what is the most dominant factor causing poverty in Riau Province. This study aims to determine what factors are causing the poverty in Riau and how big the dominant factors affecting poverty in Riau Province. This study uses a quantitative research with an assessment of descriptive data. In collecting the data, researchers use interviewing techniques, study literature, and the collection of secondary data from relevant agencies. In the data analysis researchers used multiple linear regression analysis.From the analysis of quantitative descriptive data that the causes of poverty in Riau Province is economic growth, education, unemployment and employment and the most dominant influence on poverty in Riau province is unemployment.Keywords: poverty, economic growth, education, unemployment, and employment.